2012
DOI: 10.1007/s10453-012-9281-z
|View full text |Cite
|
Sign up to set email alerts
|

Microbial communities adhering to the obverse and reverse sides of an oil painting on canvas: identification and evaluation of their biodegradative potential

Abstract: In this study, we investigated and compared the microbial communities adhering to the obverse and the reverse sides of an oil painting on canvas exhibiting signs of biodeterioration. Samples showing no visible damage were investigated as controls. Air samples were also analysed, in order to investigate the presence of airborne microorganisms suspended in the indoor atmosphere. The diversity of the cultivable microorganisms adhering to the surface was analysed by molecular techniques, such as RAPD analysis and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 39 publications
3
42
1
Order By: Relevance
“…These airborne particles can be deposited on the works of art, and under favourable conditions of temperature, humidity, light and substrate, they can use the different surfaces not just as a physical support for their growth, but also as a nutrient source. This can cause irreversible structural changes or damage to such protected works of art, with a loss of strength and structure, and also changes from an aesthetic point of view (Lopez-Miras et al, 2013). To avoid irreversible deterioration of such artefacts, and to evaluate the indoor biological risk, it is important to periodically carry out aerobiological monitoring of the biological components of the air of their environment, which provides the characterisation of the air quality from a biological point of view, both quantitatively (e.g., degree of contamination) and qualitatively (e.g., presence of potentially biodeteriogens species or with potential allergenicity) (Gravesen, 1979;Kurup et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…These airborne particles can be deposited on the works of art, and under favourable conditions of temperature, humidity, light and substrate, they can use the different surfaces not just as a physical support for their growth, but also as a nutrient source. This can cause irreversible structural changes or damage to such protected works of art, with a loss of strength and structure, and also changes from an aesthetic point of view (Lopez-Miras et al, 2013). To avoid irreversible deterioration of such artefacts, and to evaluate the indoor biological risk, it is important to periodically carry out aerobiological monitoring of the biological components of the air of their environment, which provides the characterisation of the air quality from a biological point of view, both quantitatively (e.g., degree of contamination) and qualitatively (e.g., presence of potentially biodeteriogens species or with potential allergenicity) (Gravesen, 1979;Kurup et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Micro-organisms may have played a major role in the deterioration of the wooden painting, as the high cellulose content of the artwork promotes its susceptibility to microbial deterioration (Okpalanozie et al 2016). Species from the genus Penicillium are common colonizers of paintings (L opez-Miras et al 2013) where they proliferate due to their cellulolytic activity (Seves et al 1996). However, our results showed that strains of A. flavus had higher I CMC values than P. citrinum.…”
Section: Resultsmentioning
confidence: 64%
“…Species from the genus Penicillium are common colonizers of paintings (López‐Miras et al . ) where they proliferate due to their cellulolytic activity (Seves et al . ).…”
Section: Resultsmentioning
confidence: 99%
“…Previous work demonstrated that some Actinobacteria are potentially harmful to the preservation of cultural relics [18][19][20]. Proteobacteria are commonly the most abundant bacteria in soil [21,22], and…”
Section: Discussionmentioning
confidence: 99%